Magnetoencephalography study of the effect of attention modulation on somatosensory processing in patients with major depressive disorder. Issue 2 (31st October 2015) - Kurita, Sumie; Takei, Yuichi; Maki, Yohko; Hattori, Suguru; Uehara, Toru; Fukuda, Masato; Mikuni, Masahiko
Abstract : Aims: Although affective and/or attention modulation of somatosensory processing has been well studied, the biological bases of somatic symptoms in patients with major depressive disorder (MDD) have rarely been examined. To elucidate changes in somatosensory processing underlying somatic symptoms in patients with MDD, we conducted a magnetoencephalography study of patients with MDD and healthy controls. Methods: After median nerve stimulation, somatosensory evoked fields (SEF) were recorded in 10 patients with MDD and 10 sex‐, age‐, and height‐matched healthy volunteers under somatosensory attending, visually attending, and non‐attending conditions. The latencies and magnitudes of N20m and P60m SEF were examined. Results: In the MDD group, P60m latency was significantly prolonged, irrespective of attention modulation, whereas N20m latency and root mean squares N20m and P60m amplitudes remained unchanged. Prolonged P60m latency negatively correlated with the somatosensory threshold, which was relatively high in the MDD group. Prolonged P60m latency also negatively correlated with a state of anxiety during the examination, but not with depressive symptoms or psychotropic medication. Conclusions: These results suggested that patients with MDD experience dysfunction in somatosensory information processing, approximately 60 ms after stimuli, irrespective of attentional conditions.